Khamseen rock shelter and the Late Palaeolithic‐Neolithic transition in Dhofar. (18th April 2013) - Hilbert, Yamandú H.
Abstract : This paper presents the archaeological site of Khamseen rock shelter, its stratigraphic succession, numeric ages and Early–Middle Holocene lithic assemblages. The site was discovered and excavated during the 2010 fieldwork campaign of the Dhofar Archaeological Project (DAP) in southern Oman. It is situated at the southern edge of the Nejd Plateau, strategically positioned adjacent to a major orographic barrier at the interface of the plateau and escarpment. Excavations revealed a succession of five archaeological horizons, each bearing technologically distinct lithic assemblages. The lowest level (GH.5) is attributed to the Khashabian industry, representing the final phase of the South Arabian Late Palaeolithic. Above that, in GH.4, a Neolithic assemblage was found with bifacial tool forms typical of the Middle Holocene. In light of the evidence found at Khamseen rock shelter and other coeval archaeological sites across southern Arabia, the Late Palaeolithic‐Neolithic transition is considered.